Short-coupled polymorphic ventricular tachycardia at rest linked to a novel ryanodine receptor (RyR2) mutation: Leaky RyR2 channels under non-stress conditions. (1st February 2015) - Cheung, Jim W.; Meli, Albano C.; Xie, Wenjun; Mittal, Suneet; Reiken, Steven; Wronska, Anetta; Xu, Linna; Steinberg, Jonathan S.; Markowitz, Steven M.; Iwai, Sei; Lacampagne, Alain; Lerman, Bruce B.; et al.
Abstract: Background: Ryanodine receptor (RyR2) mutations have largely been associated with catecholaminergic polymorphic ventricular tachycardia (PMVT). The role of RyR2 mutations in the pathogenesis of arrhythmias and syncope at rest is unknown. We sought to characterize the clinical and functional characteristics associated with a novel RyR2 mutation found in a mother and daughter with PMVT at rest. Methods and results: A 31-year-old female with syncope at rest and recurrent short-coupled premature ventricular contractions (PVCs) initiating PMVT was found to be heterozygous for a novel RyR2-H29D mutation. Her mother, who also had syncope at rest and short-coupled PMVT, was found to harbor the same mutation. Human RyR2-H29D mutant channels were generated using site-directed mutagenesis and heterologously expressed in HEK293 cells together with the stabilizing protein calstabin2 (FKPB12.6). Single channel measurements of RyR2-H29D mutant channels and wild type (WT) RyR2 channels were compared at varying concentrations of cytosolic Ca 2 + . Binding affinities of the RyR2-H29D channels and RyR2-WT channels to calstabin2 were compared. Functional characterization of the RyR2-H29D mutant channel revealed significantly higher open probability and opening frequency at diastolic levels of cytosolic Ca 2 + under non-stress conditions without protein kinase A treatment. This was associated with a modest depletion of calstabin2 binding under resting conditions. Conclusions: The RyR2-H29D mutation is associated with a clinical phenotype of short-coupled PMVT at rest. In contrast to catecholaminergic PMVT-associated RyR2 mutations, RyR2-H29D causes a leaky channel at diastolic levels of Ca 2 + under non-stress conditions. Leaky RyR2 may be an under-recognized mechanism for idiopathic PMVT at rest. Highlights: A ryanodine receptor mutation (RyR2-H29D) linked to PMVT at rest is found. Single channel studies on mutant RyR2-H29D channels and wildtype channels were done. RyR2-H29D mutant channels have higher open probability under non-stress conditions. Unlike CPVT-associated RyR2 mutations, RyR2-H29D leads to arrhythmias at rest.